Extracellular chloride regulation of Kv2.1, contributor to the major outward Kv current in mammalian outer hair cells - Li, Xiantao (American Physiological Society, 2012)
Outer hair cells (OHC) function as both receptors and effectors in providing a boost to auditory reception. Amplification is driven by the motor protein prestin, which is under anionic control. Interestingly, we now find that the major, 4-AP-sensitive, outward K(+) current of the OHC (I(K)) is also sensitive to Cl(−), although, in contrast to prestin, extracellularly. I(K) is inhibited by reducing extracellular Cl(−) levels, with a linear dependence of 0.4%/mM. Other voltage-dependent K(+) (Kv) channel conductances in supporting cells, such as Hensen and Deiters' cells, are not affected by reduced extracellular Cl(−). To elucidate the molecular basis of this Cl(−)-sensitive I(K), we looked at potential molecular candidates based on Cl(−) sensitivity and/or similarities in kinetics. For I(K), we identified three different Ca(2+)-independent components of I(K) based on the time constant of inactivation: a fast, transient outward current, a rapidly activating, slowly inactivating current (Ik(1)), and a slowly inactivating current (Ik(2)). Extracellular Cl(−) differentially affects these components. Because the inactivation time constants of Ik(1) and Ik(2) are similar to those of Kv1.5 and Kv2.1, we transiently transfected these constructs into CHO cells and found that low extracellular Cl(−) inhibited both channels with linear current reductions of 0.38%/mM and 0.49%/mM, respectively. We also tested heterologously expressed Slick and Slack conductances, two intracellularly Cl(−)-sensitive K(+) channels, but found no extracellular Cl(−) sensitivity. The Cl(−) sensitivity of Kv2.1 and its robust expression within OHCs verified by single-cell RT-PCR indicate that these channels underlie the OHC's extracellular Cl(−) sensitivity.